TOTAL PROTEIN ALTERATION IN TISSUE OF FRESHWATER SNAIL, THIARA TUBERCULATA DURING CYPERKILL EXPOSURE - MULE, M.B.; LOMTE, V. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The freshwater gastropod Thiarsa tuberculata from Kham river at Aurangabad were exposed to lethal and sublethal concentrations (2.82 ppm and 0.69 ppm) of cyperkill as acute and chronic treatment. Biochemical study shows the alteration of protein content in exposed tissues. In acute treatment by cyperkill the protein content of whole body decreased significantly (p<0.01), but after chronic treatment protein change was not significant. The protein content of foot and mantle remained stable in treatment. In digestive gland most significant (p<0.001) decrease of protein content was found after acute and chronic treatment. The decrease of protein after treatment was maximum in digestive gland followed by foot and mantle.